2021
DOI: 10.3389/fphar.2021.793586
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Reveals the Protective Effects of Empagliflozin on Lipid Metabolism in Nonalcoholic Fatty Liver Disease

Abstract: Empagliflozin is a novel type of sodium-glucose cotransporter two inhibitor with diverse beneficial effects in the treatment of nonalcoholic fatty liver disease (NAFLD). Although empagliflozin impacts NAFLD by regulating lipid metabolism, the underlying mechanism has not been fully elucidated. In this study, we investigated transcriptional regulation pathways affected by empagliflozin in a mouse model of NAFLD. In this study, NAFLD was established in male C57BL/6J mice by administration of a high-fat diet; it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Consistent with our previous study, the HFD-induced metabolic disturbance was improved by EMPA treatment (p < 0.05). 18 , 20
Figure 1 Mouse biochemistry parameters (A–J) (A) body weight, (B) fat mass, (C) fat/body weight, (D) serum triglyceride, (E) fasting glucose, (F) fasting insulin, (G) homeostatic model assessment of insulin resistance (HOMA-IR) index, (H) free fatty acids (FFA), (I) oral glucose tolerance test (OGTT), and (J) insulin tolerance test (ITT) curve. ∗p < 0.05, ∗∗p < 0.01, for (E) and (F), ∗HFD vs. CT p < 0.05, # EMPA vs. HFD, n = 5–6.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with our previous study, the HFD-induced metabolic disturbance was improved by EMPA treatment (p < 0.05). 18 , 20
Figure 1 Mouse biochemistry parameters (A–J) (A) body weight, (B) fat mass, (C) fat/body weight, (D) serum triglyceride, (E) fasting glucose, (F) fasting insulin, (G) homeostatic model assessment of insulin resistance (HOMA-IR) index, (H) free fatty acids (FFA), (I) oral glucose tolerance test (OGTT), and (J) insulin tolerance test (ITT) curve. ∗p < 0.05, ∗∗p < 0.01, for (E) and (F), ∗HFD vs. CT p < 0.05, # EMPA vs. HFD, n = 5–6.
…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that EMPA can protect against obesity-related cardiac dysfunction, nonalcoholic fatty liver disease, and chronic kidney disease via different mechanisms. 18 , 19 , 20 This protection was associated with improving metabolic disruption, including a reduced fat/body weight ratio and restored glucose homeostasis. Our study further confirmed that EMPA can reduce the fat/body weight ratio and alleviate impaired glucose/insulin tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNA sequence and data analysis were prepared as previously described by our group (19). Differentially expressed genes (DEGs) were identified using limma packages in R 4.0.3 with the default parameters at (logFC) > 1, P.Value < 0.05 for the groups.…”
Section: Rna-seq and Data Analysismentioning
confidence: 99%
“…NAFLD pathophysiology depends on multiple constituents like hepatic lipid accumulation, IR, oxidative stress, endoplasmic reticulum stress, and other injuries. EMPA is found to be efficacious in minimizing all these aspects and thus reducing the NAFLD development [ 33 - 35 ].…”
Section: Reviewmentioning
confidence: 99%